Design and Implementation of a Smart Home Automation System Based on Global System for Mobile Communications - Khamees, Mohanad Ghazi; Tawfeeq, Omar Al-Mukhtar; Hamad, Qusay (Journal of Applied Engineering Science, 2018)
Recently, there has been an increasing advancement in the communications technology, and due to the increment in using the cellphone applications in the diverse aspects of life, it became possible to automate home appliances, which is the desired goal from residences worldwide, since that provides lots of comfort by knowing that their appliances are working in their highest efficiency whenever it is required without their knowledge, and it also allows them to control the devices when they are away from home, including turning them on or off whenever required.   The design and implementation of this system is carried out by using the Global System of Mobile communications (GSM) technique to control the home appliances – In this work, an electric fan is used, and a sounding buzzer is used as well – and that is through the utilization of Short Message Services (SMS).   Besides that, an Arduino board has been integrated with a number of sensors such as a motion sensor, a temperature sensor, and a screen for displaying required information to the user which indicates whatever the system is doing, where this data includes the state of appliances, where the Arduino board can control the home appliances through the relay board that accepts low power signals, and based upon them, it activates high power devices.